Egg albumen templated graphene foams for high-performance supercapacitor electrodes and electrochemical sensors. Issue 37 (13th September 2018) - Liu, Ya; Zhao, Xiaoli; Wang, Cancan; Zhang, Long; Li, MengXiong; Pan, Yunmei; Fu, Yifeng; Liu, Johan; Lu, Hongbin
Abstract : Biocompatible N, S, and Si co-doped graphene foams for high-performance supercapacitor electrodes and electrochemical sensors were prepared. Abstract : We demonstrate a simple and scalable strategy to obtain N, S and Si co-doped biocompatible graphene foams (GFs) with different shapes using egg albumen as the template. The unique porous structure and element doping endow the GFs with a high charge–discharge rate and good wettability, which largely improve the electrochemical performance of the electrodes, including ultrahigh specific capacitance (534 F g −1 at 1 A g −1 ), and excellent rate capability (308 F g −1 at 100 A g −1 ) and cycling performance (96.1% retention of the initial capacitance after 10 000 cycles at a high current density of 10 A g −1 ). Besides, when used as an electrochemical sensor for dopamine, the GF exhibits a detection limit as low as 1.2 μM with a linear response up to 70 μM, due to the low equivalent series resistance. These reveal great potential for promoting the application of 3D graphene in energy storage and electrochemical sensors.